From conception to perception - The meddling of the immaterial into the body; a critical appraisal of the work of EMBAIXADA - Griff, Nuno Bernardo; Mendonça, Cristina de; Goinhas, Paulo Albuquerque (Arhitektura i urbanizam, 2018)
The purpose of this work is to explore a tabu: the gap between the disciplinary realm of architectural practice and the lived dimension of a construction, that is to say the inconsistency between architecture as a conceptual and intellectual enterprise and reality. The case study project is a reconversion of a former rundown infrastructure that once played a relevant role in the social and urban context of the city of Tomar in Portugal. The project achieved recognition among peers, won several architecture awards, was proposed for the Mies Van der Rohe award 2009, and is one of the forty buildings selected to represent the Portuguese contemporary heritage. Without disclaiming the validity of those interpretations, we took this opportunity to review our own project with the introduction of external forces of reality [namely human, social and political] into the “processes” and “products” of architectural practice. Our aim is to use this ontological problematic [objectivity vs. Subjectivity] to see if the conceptual intentions of the project could withstand [or not] the engagement with the complex reality of everyday life – people, time and function. And more important, what kind of new spatial possibilities it opened. This research, more than the production of a systematic inquiry, will help towards a meta-reflection about architectural practice, in order to unveil and clarify aspects considered as implicit, with the purpose of identifying the limits of our profession and to improve the meaning of our production, which, after all it’s the meaning of our own lives.